TRANSITION RS: the design component for the communication of medical research - Angari, Roberta; Pontillo, Gabriele; Langella, Carla; Piscitelli, Daniela (InfoDesign, 2021)
Over the last few years, design has increasingly entered the realm of health, thanks to the connection with other disciplines, such as science and medicine. Information design, due to its ability to translate complex and invisible data into visible and understandable ones, can put the interpretative filter of contemporary scientific research over product, services and communicative artifacts, useful to transmit to people knowledge related to psycho-physical well-being. In addition to being associated with more conscious choices and activities, information design and, as well, design, through the connection with medicine, can help in the communication of diseases, both for treatment and preservation. The aim of the paper is to introduce the methodology and, as well, the firsts results of an ongoing research which focus is the divulgation of medical-scientific knowledge on Neurofibromatosis Type 1 (NF1) and epigenetic factors, which technical data have been translated into different king of devices able to relate people everyday life with the managing and prevention of this pathology.